Business communication - Debasish, Sathya Swaroop (PHI Learning, 2010)
Effective communication is the foundation of sound management. Regardless of the size of the business we are in - a multinational company, a medium enterprise or a small-scale industry - effective communication skills are always needed for success. This comprehensive book dwells onto all aspects of business communication which helps to attain success in a business. This book is organized in three sections. Section-I (Basics of Communication) details on how messages in business should be conveyed clearly and unambiguously through various models of communication. It further explains that a message when communicated effectively can help in selling the concept, goods, products or services more conveniently and effectively. Section-II (Oral and non-verbal communication) elucidates that besides verbal communication, non-verbal communication such as gestures, postures, dressing and hair style also plays an equal and important role in imparting messages in a corporate environment. Section-III (Written communication) details on the factors which help to enhance the business writing abilities (letters and memos). Besides, the book teaches various other aspects of business communication like how to prepare for an interview, how to conduct a meeting and also how to draft an impressive resume. Primarily intended for the postgraduate students of management, the book is equally beneficial for the business professionals and company owners, to help them learn the traits of effective communication.